Effect of Volatile Anesthetics on Myocardial Infarction After Coronary Artery Surgery: A Post Hoc Analysis of a Randomized Trial - Zangrillo, Alberto; Lomivorotov, Vladimir V; Pasyuga, Vadim V; Belletti, Alessandro; Gazivoda, Gordana; Monaco, Fabrizio; Nigro Neto, Caetano; Likhvantsev, Valery V; Bradic, Nikola; Lozovskiy, Andrey; Lei, Chong; Bukamal, Nazar A R; et al. (Journal of cardiothoracic and vascular anesthesia, 2022)
OBJECTIVE: To investigate the effect of volatile anesthetics on the rates of postoperative myocardial infarction (MI) and cardiac death after coronary artery bypass graft (CABG). DESIGN: A post hoc analysis of a randomized trial. SETTING: Cardiac surgical operating rooms. PARTICIPANTS: Patients undergoing elective, isolated CABG. INTERVENTIONS: Patients were randomized to receive a volatile anesthetic (desflurane, isoflurane, or sevoflurane) or total intravenous anesthesia (TIVA). The primary outcome was hemodynamically relevant MI (MI requiring high-dose inotropic support or prolonged intensive care unit stay) occurring within 48 hours from surgery. The secondary outcome was 1-year death due to cardiac causes. MEASUREMENTS AND MAIN RESULTS: A total of 5,400 patients were enrolled between April 2014 and September 2017 (2,709 patients randomized to the volatile anesthetics group and 2,691 to TIVA). The mean age was 62 ± 8.4 years, and the median baseline ejection fraction was 57% (50-67), without differences between the 2 groups. Patients in the volatile group had a lower incidence of MI with hemodynamic complications both in the per-protocol (14 of 2,530 [0.6%] v 27 of 2,501 [1.1%] in the TIVA group; p = 0.038) and as-treated analyses (16 of 2,708 [0.6%] v 29 of 2,617 [1.1%] in the TIVA group; p = 0.039), but not in the intention-to-treat analysis (17 of 2,663 [0.6%] v 28 of 2,667 [1.0%] in the TIVA group; p = 0.10). Overall, deaths due to cardiac causes were lower in the volatile group (23 of 2,685 [0.9%] v 40 of 2,668 [1.5%] than in the TIVA group; p = 0.03). CONCLUSIONS: An anesthetic regimen, including volatile agents, may be associated with a lower rate of postoperative MI with hemodynamic complication in patients undergoing CABG. Furthermore, it may reduce long-term cardiac mortality.
Keywords: Anesthetics, Intravenous; Humans; Coronary Artery Bypass; lidé středního věku; propofol; Aged; Anesthetics, Inhalation; sevofluran; cancer; senioři; lidé; infarkt myokardu; cardioprotection; Postoperative Complications; anestetika inhalační; volatile anesthetics; anestetika intravenózní; pooperační komplikace; mortality; Propofol; Middle Aged; koronární bypass; Myocardial Infarction; myocardial infarction; Sevoflurane; cardiac surgery